Sixteenths: direct evidence on institutional execution costs - Jones, Charles M; Lipson, Marc L (Journal of Financial Economics, 2001)
In June 1997, the New York Stock Exchange lowered its minimum price increment on most stocks from eighths to sixteenths. We use a sample of institutional trades to directly measure the effect of this tick size reduction on execution costs. Though quoted and effective spreads decline, realized execution costs for these institutions increase after the change to sixteenths. Costs increase most for orders that aggressively demand liquidity, including large orders, orders placed by momentum traders, and orders not worked by the trading desk. These findings emphasize that spreads are not a sufficient statistic for market quality. Smaller tick sizes may actually reduce market liquidity.